The Interrelation between Islamic Law and Regional Regulations in Jember (Examining the Maqāṣid al-Sharī‘at-based Reasoning in Istinbāṭ al-Ahkām) - Muhaimin Muhaimin (AHKAM : Jurnal Ilmu Syariah, 2020)
This study reviews the dichotomous concept of secular and shari’a laws. Such concept has led to new discourses: first, shari’a can influence national (modern) law without mentioning the Islamic framework in the formulation process. Second, the shari’a can stand on its own for particular religious groups who believe in its truth and place it in a higher position than the secular law. Third, the substance of shari’a and modern laws is integrable. This study uses an anthropological-sociological approach with Maqāṣid al-Sharī‘at framework. As a result, the study shows both national and regional legal products, on the one hand, are considered as the shari’a law as long as they are beneficial to and protect all people. On the other hand, the shari’a, which substantially reflects equality and fairness, can be claimed as modern law.     AbstrakStudi ini mengkaji konsep dikotomis hukum sekuler dan shari’a. Konsep tersebut melahirkan wacana-wacana baru: pertama, shari’a dapat mempengaruhi hukum nasional (modern) tanpa menyebutkan kerangka Islam dalam proses perumusannya. Kedua, shari’a dapat berdiri sendiri bagi kelompok agama tertentu yang meyakini kebenarannya dan menempatkannya pada posisi yang lebih tinggi dari hukum sekuler. Ketiga, substansi shari’a dan hukum modern terintegrasi. Penelitian ini menggunakan pendekatan antropologis-sosiologis dengan kerangka Maqāṣid al-Sharī‘at. Studi ini menyimpulkan bahwa produk hukum nasional dan daerah di satu sisi dianggap sebagai hukum shari’a selama bermanfaat dan melindungi semua orang. Di sisi lain, shari’a yang secara substansial mencerminkan kesetaraan dan keadilan dapat diklaim sebagai hukum modern.